Textual cohesion special characteristics for knowing styles of Persian literature - علی‌رضا احمدی; اصلان استواری (مطالعات زبانی و بلاغی)
The present research is an attempt to investigate and compare textual cohesion in khorasani and Iraqi styles. As suchâ the stories of â³Hasanak vazirâ³ and â³Afshin an Budolof from Tarikh Beyhaghi are examples of Khorasani style and stories of â³Shir and Ghavâ³ and â³Buf and Zaghâ³ from â³Kelileh and Demneâ³ as examples of Iraqi Style were analyzed and compared based on the model introduced by Halliday and Hassan (1976). The results of the study indicated that in both styles the linking factors were used more than grammatical and lexical factors. In generalâ 39.82 % of the whole lexical items in â³Tarikh Beyhaghiâ³ were those that made textual cohesion possible. This number declined to 24.86% in Kelileh and Demneh. The chi-square test was also used in order to see whether the difference between cohesive elements in the two styles were significantly different or not. It was found out that in many cases the difference was significant leading to the conclusion that the Khorasani and Iraqi styles are significantly different in terms of textual cohesion. According to the obtained results one canâ in view of textual cohesionâ consider special characteristics for Persian literature based on which the texts of Persian literature can be compared and classified.